Behaviour and breeding success of gentoo penguins Pygoscelis papua in areas of low and high human activity - Holmes, ND; Giese, MA; Achurch, H; Robinson, S; Kriwoken, LK (2006)
A key factor influencing wildlife responses to human activity is the degree to which animals have been previously exposed to human stimuli. On subantarctic Macquarie Island, gentoo penguins Pygoscelis papua breed in areas of high and low human activity (on and off-station, respectively). We investigated the behaviour and breeding success of gentoo penguins on and off-station, by a) comparing the behavioural responses of guarding gentoos before, during and after exposure to standardised pedestrian approaches, and b) employing an observational study to determine how human activity may have contributed to within-season breeding success in light of other environmental and site variables. Behavioural responses to pedestrian visitation by gentoos off-station were significantly stronger than those of birds breeding on-station. However, no relationship was found between pedestrian activity and breeding success off-station. Breeding success was, however, positively related to colony size, and negatively related to the activity of other penguins, the number of nearby southern elephant seal Mirounga leonina harems and the location of colonies within short grassland. On-station, breeding success was amongst the highest recorded for that season. Habituation, predator exclusion and the relevance of these findings for management are discussed. Â© Springer-Verlag 2005.